Introductory Statistics - Mann, Prem S. (John Wiley & Sons Singapore Pte.Ltd, 2024)
Introductory Statistics, 10th edition, is written for a one- or two-semester first course in applied statistics and is intended for students who do not have a strong background in mathematics. The only prerequisite is knowledge of elementary algebra. Known for its realistic examples and exercises, clarity and brevity of presentation, and soundness of pedagogical approach, the book encourages statistical interpretation and literacy regardless of student background. The book employs a clear and straightforward writing style and uses abundant visuals and figures, which reinforce key concepts and relate new ideas to prior sections for a smooth transition between topics. This international edition offers new and updated materials and focuses on strengthening the coverage by including new sections on types of scales, negative binomial distribution, and two-way analysis of variance. Additionally, discussions on ogive curves, geometric mean, and harmonic mean have also been added. Many examples and exercises throughout the book are new or revised, providing varied ways for students to practice statistical concepts